Ваточник звичайний (Asclepias syriaca L., Apocynaceae Juss.) – інвазійно небезпечний медонос флори України - Діденко, В.І.; Куземко, А. А.; Безсмертна, Олеся Олексіївна; Шиндер, О.І.; Кучер, О.О.; Шевчик, Василь Леонович; Подобайло, Анатолій Віталійович; Костіков, Ігор Юрійович (Національний науковий центр «Інститут бджільництва імені П.І.Прокоповича», Інститут біології тварин НААН України, 2022)
Introduction. Data on the distribution of one of the highly invasive species of the flora of Ukraine – common milkweed (Asclepias syriaca L., Apocynaceae), its honey-bearing properties and recommendations for population control and prevention of further invasions have been presented. The goal of the work. Based on the analysis of data on the history of naturalization in Ukraine, biological, phytocenotic, molecular genetic features related to the invasive potential, impact on natural communities, and the approval of methods of control of the common milkweed, give an answer to the question about the possibility and conditions of introducing A. syriaca into beekeeping practice. Material and methods of research. Сritical analysis of literary sources, their comparison and generalization, monitoring observations, field investigations, phytocenotic methods, as well as bioinformatics method. Results of research and discussion. According to litery sources and personal observation of the authors A. syriaca is a component of communities of the anthropogenic vegetation of the Epilobietea angustifolii, Artemisietea vulgaris, Robinietea classes, and more rarely natural and semi-natural communities of Festuco-Brometea, Molinio-Arrhenatheretea, Trifolio-Geranietea sanguinei, Koelerio-Corynephoretea canescentis. The species prefer disturbed open areas, where it is usually dominant, displacing native species. Common milkweed is an excellent honey bearer. However, despite the high honey productivity of 600 kg/ha, the need to control its population is substantiated, in particular, the use of multiple, long-term, annual mowing to prevent further invasions of natural ecosystems and loss of biodiversity. Hybridization is not the cause of the high invasiveness of the common milkweed because of sites with ambiguously identified nucleotides, which is one of the signs of hybridogenesis was not detected. Conclusions and prospects for further research. Despite its economic value, including significant honey-producing properties, A. syriaca is a dangerous invasive species that causes loss of biodiversity and reduces crop yields. We believe that cottonwood should be included in the list of quarantine weeds in Ukraine and its cultivation should be prohibited.

Наводяться дані про поширення високоінвазійного виду флори України – ваточника звичайного (Asclepias syriaca L., Apocynaceae). Вид приурочений до порушених відкритих ділянок, де виступає домінантом, витісняючи аборигенні види. Є широко розповсюдженою інвазійною рослиною у європейських країнах, де включений до офіційного переліку чужорідних інвазійних видів, проте в Україні не є карантинним об’єктом. Ваточник звичайний є чудовим медоносом, але, з метою запобігання подальших інвазій у природні екосистеми, обґрунтовується необхідність контролю його чисельності шляхом щорічного скошування.
Keywords: адвентивний вид; біорізноманіття; гібридизація; інвазійний вид; фітоінвазія; фітоценоз; alien species; invasive species; biodiversity; hybridization; phytocenosis; phytoinvasion